Influence of severe cold thermal environment on thermal sensation and physiological responses - Tomi Zlatar (2019)
Exposure to cold affects health and poses significant risks for cardiovascular diseases, musculoskeletal complaints and symptoms. It is present in outdoor activities in high latitude environments and within different occupations, causing variations in core and skin body temperatures and affecting working performance, health and safety. This work aims to evaluate the changes in thermal sensation, and in some physiological parameters before, during and after exposure to the severe cold thermal environment (SCE) (20 °C) of subjects wearing cold protective equipment. By using the Thermal Sensation Questionnaire (TSQ), blood pressure equipment, thermometer telemetry capsules and 8 skin temperature sensors, a study was conducted on 11 non-acclimatized male volunteers with a 60-minute exposure. The results show variations in all measured parameters. Findings evidence decreases in located skin temperatures and recovery periods for each measured point and increases in core temperature despite exposure to SCE. Future studies should be conducted using more skin temperature measuring points in the extremities (face, fingers and toes). (c) Springer Nature Switzerland AG 2019.